Kemampuan Berpikir Kreatif di Indonesia : Sebuah Kajian Literatur - Utomo Aji, Singgih (Jurnal Riset Pendidikan Matematika Jakarta, 2024)
Creative thinking is one of the HOT skills that students in Indonesia are required to have. The reality in the field states that there are quite a few students whose creative thinking abilities are not honed in learning mathematics at school. This research aims to determine the concept of creative thinking and the application of creative thinking skills in Indonesia. This research is a Systematic Literature Review (SLR) research. Of the 18 articles obtained and reviewed, it is stated that creative thinking is a person's ability to obtain various new and original ideas or ideas to find solutions to problems so as to obtain several other alternative answers. The trend of research in Indonesia is to focus on creative thinking using an open ended approach.